2014
DOI: 10.1208/s12248-014-9576-9
|View full text |Cite
|
Sign up to set email alerts
|

A Priori Prediction of Tumor Payload Concentrations: Preclinical Case Study with an Auristatin-Based Anti-5T4 Antibody-Drug Conjugate

Abstract: Abstract. The objectives of this investigation were as follows: (a) to validate a mechanism-based pharmacokinetic (PK) model of ADC for its ability to a priori predict tumor concentrations of ADC and released payload, using anti-5T4 ADC A1mcMMAF, and (b) to analyze the PK model to find out main pathways and parameters model outputs are most sensitive to. Experiential data containing biomeasures, and plasma and tumor concentrations of ADC and payload, following A1mcMMAF administration in two different xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 18 publications
5
63
0
Order By: Relevance
“…Several models have been proposed to mechanistically model ADC efficacy (43)(44)(45)(46)(47)(48)(49)(50)(51)(52), many of which have been previously reviewed (41). Mechanistic models have often been applied to investigate antibodies as a modality, although modeling studies focused on immunotoxins have also been reported (43,52).…”
Section: Antibody Drug Conjugate (Adc) Platformmentioning
confidence: 99%
“…Several models have been proposed to mechanistically model ADC efficacy (43)(44)(45)(46)(47)(48)(49)(50)(51)(52), many of which have been previously reviewed (41). Mechanistic models have often been applied to investigate antibodies as a modality, although modeling studies focused on immunotoxins have also been reported (43,52).…”
Section: Antibody Drug Conjugate (Adc) Platformmentioning
confidence: 99%
“…75 Application of Quantitative Systems Pharmacology Modeling Quantitative systems pharmacology modeling was previously used for ADC design optimization, 76,77 prediction of tumor ADC concentrations, and increasing the understanding of intracellular ADC activation in preclinical tumor models. This information was then used to guide dose selection 78,79 and translate data from preclinical species to humans to predict clinically efficacious doses. 80,81 A multiscale, mechanism-based PK/PD model was built and validated using published brentuximab vedotin experimental data.…”
Section: Immunogenicity Assessmentmentioning
confidence: 99%
“…Of particular interest is the prediction of released payload concentrations at the site of therapeutic action, which may be significantly higher than the concentration observed in plasma (Alley et al, 2009). As direct clinical measurement of released payload concentrations through the use of tumor distribution studies is often logistically challenging, a significant effort has recently been placed on the development of in dmd.aspetjournals.org vitro or in silico techniques to predict the effect of therapeutic sitespecific catabolism on the observed target-site concentrations of ADC payloads (Shah et al, 2014). The final aspect of this symposium focused on the use of in vitro cellular assays to determine the effect of ADC catabolism at the site of therapeutic action on the observed pharmacodynamics of the ADC.…”
Section: Pulmonary Metabolism Of Resveratrol: In Vitro and In Vivomentioning
confidence: 99%